Meta-Analisis Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar IPS Siswa Kelas 5 Sekolah Dasar - Diah Ayu Putri Utami; Nyoto Hardjono (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this study to analyze the effect of audio visual media on the result of learning social science of 5th grade students elementary school. Audio visual media is a set of integrated tools which combines the sound, image, and than it can instill concrete the concepts that can be seen heard. First, researcher formulated the problem and then proceeded to collect researchs data that was already through google scholar. From the search, 10 articles from jurnals, 1 prociding and 1 minithesis from relevant repository. The research results from the reseacher were analyzed by quantitative comparison methods. Based on yhe results of the analysis, that audio visual media has an effect on improving the learning of 5th grade students. The effect of using audio-visual media is that can improve social studies outcomeslearning of 5th grade students of started from the lowest 12,36 % until the highest 81,81 % with an avarage increase of 31,96 %.